A time-varying index for agricultural suitability across Europe from 1500–2000 - Alexander Lehner; Dylan Philippe (Scientific Data)
Abstract Throughout the last centuries, European climate changed substantially, which affected the potential to plant and grow crops. These changes happened not just over time but also had a spatial dimension. Yet, despite large climatic fluctuations, quantitative historical studies typically rely on static measures for agricultural suitability due to the non-availability of time-varying indices. Relying on recent advances in paleoclimatology, we bridge this gap by constructing a spatio-temporal measure for agricultural suitability across Europe for a period of 500 years. Our gridded index has a 0.5° resolution and is available at a yearly level. It relies on a simple surface energy and water balance model, focusing only on so-called exogenous geographic and climatic features. Our index captures not just long-term trends, such as the Little Ice Age, but also short-term climatic shocks. It will empower researchers to explore the interplay between climatic fluctuations and Europe’s agricultural landscape, analyze human responses at a local and regional scale, and foster a deeper understanding of the region’s historical dynamics.